Hydraulic Couplers and Their Attachments (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2026)
This article details the importance of hydraulic fasteners, their types, physical and chemical properties and additives that increase technological efficiency, which occupy an important place in the system of building materials. The process of solidification of hydraulic couplers in the aquatic environment, their mechanisms of strength formation and their application in modern construction have been analyzed from a scientific point of view. Also based on the effect of mineral and chemical additives on the quality of binders, environmental and economic efficiency.